Climate Data Tools (CDT) Training for the Regional Meteorological Service Center (RMSC) of Ethiopia - Faniriantsoa, Rija; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
An introductory training on Climate Data Tool (CDT) with 35 staff from both the regional meteorological service centers (RMSC) and the NMA head office’s Data and Climatology team. While CDT trainings have been conducted in the past, this is the first time such a training has been conducted with the NMA’s regional staff. Staff from all regions (except Tigray, where conflict is ongoing) were included in the training, which leveraged resources and was conducted jointly with the ACToday and AICCRA projects.